2022
DOI: 10.1097/ico.0000000000003002
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variation in Straylight in Patients With Fuchs Endothelial Corneal Dystrophy and Controls

Abstract: Purpose:The goal of this study was to investigate diurnal changes in intraocular straylight in relation to other corneal parameters and subjective complaints in patients with Fuchs endothelial dystrophy and healthy controls.Methods: This is a prospective study conducted in 2 tertiary care hospitals in Germany and the Netherlands. Patients with Fuchs endothelial dystrophy (n = 71) and healthy controls (n = 34) were included. Patients with Fuchs dystrophy were grouped by the presence of subjective complaints and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In previous studies, straylight was also higher after eye opening in Fuchs dystrophy compared with healthy corneas with a sloweddown resolution in eyes with poor hydration control. 3 The relative preservation of visual acuity compared with glare symptoms was also validated by experimental studies, whereby disability glare was affected by a small increase in stromal edema while visual acuity only started to decrease after substantial stromal swelling. 20,21 Nevertheless, the data obtained from this study serve as an approximation to what would be expected and experienced in everyday life because exact time points for lid closure at nighttime and eye opening in the morning in the intense measurement group were not controlled to include both eyes, if eligible, and sleep patterns in hospital might deviate from those at home.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In previous studies, straylight was also higher after eye opening in Fuchs dystrophy compared with healthy corneas with a sloweddown resolution in eyes with poor hydration control. 3 The relative preservation of visual acuity compared with glare symptoms was also validated by experimental studies, whereby disability glare was affected by a small increase in stromal edema while visual acuity only started to decrease after substantial stromal swelling. 20,21 Nevertheless, the data obtained from this study serve as an approximation to what would be expected and experienced in everyday life because exact time points for lid closure at nighttime and eye opening in the morning in the intense measurement group were not controlled to include both eyes, if eligible, and sleep patterns in hospital might deviate from those at home.…”
Section: Discussionmentioning
confidence: 88%
“…Visual disability can be assessed using questionnaires such as the Visual Function and Corneal Health Status (V-FUCHS) instrument, 1,2 which covers Fuchs dystrophy-specific impairment in glare, contrast sensitivity, and diurnal variation of vision frequently reported by patients. 3,4 Besides symptom burden, objective measurements include optical assessments of visual acuity and disability glare, and signs of morphological disease progression, such as an increase in the Krachmer grading scale, an increase in edema, or a decrease in effective endothelial cell density.…”
mentioning
confidence: 99%
“…This suggests infodemiological approaches can provide new understanding of specific days of the week, and hours of those days, on which particular ophthalmologic conditions are most affecting patients. Such approaches can add to the ongoing research studies to understand critical times or days for severity or treatment of symptoms and conditions outside of standard clinic hours for ocular conditions, as has also been studied for other disease [ 28 , 31 - 37 , 52 - 57 ]. We also observed that diurnal search patterns can differ by time of year for some terms, suggesting unique seasonal factors may affect the diurnal cycle of specific ocular conditions and raising the potential value of the approaches such as ours for enhancing the study of seasonal eye disease [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study included participants of two completed and one ongoing prospective single-center cohort studies (German Clinical Trials Register, DRKS00016996; 17 DRKS00020945; 18,19 DRKS00020946, ongoing) and of one completed randomized-controlled trial (ClinicalTrials.gov, NCT04140422). 20 Ethics Committee approval was obtained for all studies and this analysis.…”
Section: Study Design With Inclusion and Exclusion Criteriamentioning
confidence: 99%